Can community task groups learn from the principles of group therapy?. Issue 5 (20th October 2018) - Zanbar, Lea
ABSTRACT: An important part of a community social worker's job is leading task groups, whose members strive to create new welfare services or improve existing ones for their communities. Yet, a review of community task group literature shows that issues associated with group therapy, including group development, social roles, facilitation tools, etc., are barely addressed. The current theoretical article is aimed at demonstrating the need for community social workers to be aware of these group dynamics and their potential impact on the task groups they facilitate, and to equip themselves with the skills needed to enable the group to achieve its primary goal for the community. Furthermore, it considers the factors inhibiting the adoption and implementation of this approach. In addition, based on the theoretical discussion, the article offers, for the first time, practical suggestions for the adaptation of specific aspects of group therapy to the field of community social work.